Enhancing Project-Based Learning in STEM Education with Integrated Technology and Coding - Maspul, Kurniawan Arif (Journal of Intelligent Systems and Information Technology, 2024)
This extensive study explores the advantages and significance of incorporating technology and coding into project-based learning to improve STEM education. This integration improves students' learning experiences by encouraging computational thinking, problem-solving ability, and creativity. Collaborative coding projects promote interdisciplinary learning and a thorough comprehension of multiple subjects, while online resources and self-paced learning platforms enable students to study coding outside of the classroom. Educators can design meaningful learning experiences that match technology use with learning objectives and stimulate social connections and cooperation by embracing theories such as constructivism, TPACK, and social constructivism. Inquiry-based learning, project-based learning, and self-regulated learning are all strategies that promote student engagement and learning in integrated technology and coding. Providing resources, professional development opportunities, and technical support systems promotes in efficient implementation. Educators may develop engaging project-based learning experiences that equip students with necessary skills for the future by embracing creative techniques and incorporating technology and coding.